Impacts of covid19 on women’s mobility in Kuala Lumpur - Yong Adilah Shamsul Harumain; Teppei Osada; Suhana Koting; Melasutra Md Dali; Nur Sabahiah Abdul Sukor; Nurul Faizah Hamzah; Nurfatin Fauzi; Lillian Gungat (International Journal of Children, Women, The Elderly and Persons with Disabilities, 2022)
COVID-19 has undoubtedly led to challenges in mobility, yet the extent to which it has impacted women of different income levels and work backgrounds remains unknown. It is important to understand how the pandemic has affected women’s mobility, particularly in terms of changes and constraints in their perceived mobility. More research is thus required on mobility during and after the COVID-19 pandemic in Malaysia, especially among working women with small children. It is erroneous to assume that working women have stayed home during the pandemic, as we found that a significant number of women were and are going to work throughout this period. It will further contribute to less traffic congestion on the road by boosting women’s reliance on public transportation. Given that most previous studies on women’s travel using public transportation do not incorporate children as a key factor in women’s decision of travel mode to work or other places, this study’s survey sought to discover if women, namely mothers with younger children, are highly affected by their children’s travel needs in terms of their preference for public transportation during the COVID-19 pandemic and movement restriction order in Malaysia. Our results suggest that blue-collar women with lower income levels still travel outside their homes for work. However, their mobility was limited during the height of the pandemic due to the restricted movement order and strict standard operation procedures for public transportation. Further studies are needed to distinguish the challenges faced by women who lost their jobs during the pandemic and the changes to their mobility in the post-pandemic era.